Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1017/wet.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management Programs with Pyroxasulfone in Field Corn (Zea mays)

Abstract: Field experiments were conducted in Louisiana and Mississippi from 2011 through 2013 to evaluate crop injury, weed control, and yield in field corn following pyroxasulfone applied PRE and POST. Pyroxasulfone PRE or POST did not injure corn at any evaluation. Barnyardgrass control was not improved with the addition of any POST treatment to pyroxasulfone alone or atrazine plus pyroxasulfone PRE; however, all POST treatments increased barnyardgrass control to at least 95% at all evaluations following atrazine PRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Density and aboveground dry weight of barnyardgrass were comparable to the weedy plots for all VLCFA inhibitor herbicides except for S-metolachlor which reduced which decreased density 86% and aboveground dry weight 97% (Table 7). In other studies, pyroxasulfone (PRE) at 150 g•ai•ha −1 controlled barnyardgrass 93 to 96% in corn [9]. Yamaji et al [22] also found 100% barnyardgrass control with pyroxasulfone (PRE) at 125 to 250 g•ai•ha −1 in corn.…”
Section: Green Foxtailmentioning
confidence: 91%
See 3 more Smart Citations
“…Density and aboveground dry weight of barnyardgrass were comparable to the weedy plots for all VLCFA inhibitor herbicides except for S-metolachlor which reduced which decreased density 86% and aboveground dry weight 97% (Table 7). In other studies, pyroxasulfone (PRE) at 150 g•ai•ha −1 controlled barnyardgrass 93 to 96% in corn [9]. Yamaji et al [22] also found 100% barnyardgrass control with pyroxasulfone (PRE) at 125 to 250 g•ai•ha −1 in corn.…”
Section: Green Foxtailmentioning
confidence: 91%
“…However, weed interference with pethoxamid and S-metolachlor reduced corn yield 28 and 33%, respectively. Stephenson et al [9] in Louisiana found no yield loss with pyroxasulfone (PRE) at 125 g•ai•ha −1 in corn. Knezevic et al [13] in Nebraska reported that pyroxasulfone has to be applied PRE at approximately 195 g•ai•ha −1 to maintain corn yield comparable to 95% of the weed-free control.…”
Section: Corn and Soybean Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Merr. ), and sunflower ( Helianthus annuus L.) crops (Anonymous 2021b; Boutsalis et al 2014; Olson et al 2011; Shaner 2014; Stephenson et al 2017a, 2017b; Tanetani et al 2009). Pyroxasulfone is a low-use-rate, relatively less water-soluble herbicide compared with other chloroacetamide VLCFA elongase–inhibiting herbicides such as S -metolachlor (Shaner 2014; Westra 2012).…”
Section: Introductionmentioning
confidence: 99%